Avaliação da heme oxigenase 1 no pré-condicionamento nefrotóxico in vivo e in vitro - Silva, Fernanda Duarte da [UNIFESP] (2018)
Nephrotoxicity is one of the major side effects of aminoglycoside antibiotics such as Gentamicin (Genta). Preconditioning (PC) refers to the situation in which an organ or tissue subjected to an aggression acquires resistance or responds less intensely when a new aggression is repeated. The mechanism of CP is well studied, it is believed that mechanisms such as increased activity of antioxidant enzymes such as Hemeoxygenase 1 (HO1) may be involved. Objective: To study the participation of Heme oxygenase 1 (HO1) and the nephroprotective effect of PC induced by Genta in vivo and in vitro. Methods In vivo: Wistar rats were divided into Control (CTL), Genta treated animals for 10 consecutive days (IU), animals treated with Genta and Hemin for 10 consecutive days (IU + HEMIN), animals preconditioned with Genta ID) and animals preconditioned with Genta and treated concomitantly with Hemin (ID + HEMIN). Blood and urine samples were collected before and after treatment (groups IU and IU + HEMIN) and postCP (ID and ID + HEMIN groups) for analysis of creatinine, urea, sodium excretion fraction, urinary peroxides, lipid peroxidation, protein carbonylated, plasma antioxidant fraction, enzymatic activity (SOD and CAT). Animals were sacrificed and kidneys removed for immunohistochemistry for SOD and CAT. Methods In vitro: Human proximal tubule (HK2) cells were subdivided into control (CTL) groups, treated with Genta for 24h (IU), cells treated with Genta and the HO1 inducer for 24hs (IU + HEMIN). cells treated with Genta and the HO1 inhibitor for 24h concomitantly (IU + ZNPP), cells preconditioned with Genta and exposed to the antibiotic after 9 days (ID), Insulto double associated with the inducer of HO1 (ID + HEMIN ) and double insult associated with the HO1 inhibitor (ID + ZNPP). Necrosis and apoptosis were evaluated, respectively, by the Acridine Orange / Etho Bromide and Hoescht 33342 dyes. The expression of HO1 was performed by Western Blot. Results: Rats treated with Genta for 10 consecutive days (UI) presented an increase in plasma creatinine, urea, proteinuria, and sodium excretion fraction, characterizing the Nephrotoxic AKI model. The PC (ID) protected the animals from increasing these parameters. We observed increased urinary, lipid peroxides and carbonylated protein in the UI group in relation to the CTL and PC (ID) group. Conversely we observed an increase in the antioxidant fraction of the plasma, as well as an increase in the immunostaining for antioxidant enzymes (superoxide dismutase1 and catalase) in the PC group in relation to the other groups. Interestingly, the HO1 (Hemin) inducer potentiated these effects. In the main target of Genta, the proximal tubular cell, PC inhibited cell death by antibioticinduced necrosis and apoptosis, and Hemin potentiated the protective effect of CP on viability. Conclusion: PC protected the animals from GENT induced by GENT and this effect was mediated by the inhibition of oxidative stress, by direct action in the proximal tubular cell and induction of antioxidant enzymes, such as HO1, which may be a potential alternative in treatment nephrotoxic ARF by aminoglycosides.